Explorations in Augustine's Anthropology - Dalpra, Fabio; Jacobsen, Anders-Christian (Early Christianity in the Context of Antiquity, 2021)
What is a human being according to Augustine of Hippo? This question has occupied a group of researchers from Brazil and Europe and has been explored at two workshops during which the contributors to this volume have discussed anthropological themes in Augustine's vast corpus. In this volume, the reader will find articles on a wide spectrum of Augustine's anthropological ideas. Some contributions focus on specific texts, while others focus on specific theological or philosophical aspects of Augustine's anthropology. The authors of the articles in this volume are convinced that Augustine's anthropology is of major importance for how human beings have been understood in Western civilization for better or for worse. The topic is therefore highly relevant to present times in which humanity is under pressure from various sides.